1990
DOI: 10.1007/bf00035829
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis in cell cultures of birch (Betula pendula Roth.)

Abstract: Somatic embryogenesis was induced in cell cultures of birch (Betula pendula Roth.) derived from juvenile tissue of seed embryos and from mature leaf tissue. Embryos were formed in liquid and on solidified medium containing 2,4-dichlorophenoxyacetic acid (2,4-D) and 6-furfurylaminopurine (kinetin). Sometimes somatic embryos formed only after transfer to medium devoid of growth regulators. The embryos germinated on hormone-free medium and were potted in soil and grown in the greenhouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
1
19
1
Order By: Relevance
“…This induction period is longer than that seen in the present work, in which the development of embryogenic callus and somatic embryos were seen after only three months of in vitro cultivation. The results of this simultaneous use of two auxin sources to induce embryogenic callus was quite different from that reported by other authors (Kurten et al, 1990;Mathew and Philip, 2003) Martini et al (2001), who observed an inhibiting action of the BA on induction and proliferation, in orchid (Gongora quinquenervis) callus. According to Williams and Maheswaran (1986), BA acts strongly in inducing cell polarity and favors the differentiation process of embryogenic callus material.…”
Section: Resultscontrasting
confidence: 96%
“…This induction period is longer than that seen in the present work, in which the development of embryogenic callus and somatic embryos were seen after only three months of in vitro cultivation. The results of this simultaneous use of two auxin sources to induce embryogenic callus was quite different from that reported by other authors (Kurten et al, 1990;Mathew and Philip, 2003) Martini et al (2001), who observed an inhibiting action of the BA on induction and proliferation, in orchid (Gongora quinquenervis) callus. According to Williams and Maheswaran (1986), BA acts strongly in inducing cell polarity and favors the differentiation process of embryogenic callus material.…”
Section: Resultscontrasting
confidence: 96%
“…Somatic embryogenesis of birch [10] has attracted attention in plant biotechnology because it can provide a useful system for producing tree clones. For the biotechnical application of somatic embryos, differentiation and plant regeneration must be properly indicated and controlled in embryogenic cell cultures.…”
mentioning
confidence: 99%
“…Initiation material for silver birch somatic embryogenesis has been either young zygotic embryos (Kurtén et al 1990) or mature leaf tissues (Kurtén et al 1990, Hvoslef-Eide andCorke 1997). Both embryogenic and non-embryogenic cell lines have been observed in silver birch cell cultures (Kurtén et al 1990, Nuutila andKauppinen 1992).…”
Section: Silver Birch Clonesmentioning
confidence: 99%
“…Both embryogenic and non-embryogenic cell lines have been observed in silver birch cell cultures (Kurtén et al 1990, Nuutila andKauppinen 1992). PuupponenPimiä et al (1993) reported the characterization of the silver birch embryogenic BP8 gene, which is a potential genetic indicator of embryogenic cells.…”
Section: Silver Birch Clonesmentioning
confidence: 99%